2011
DOI: 10.1002/etc.646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β‐endosulfan on the growth and reproduction of zebrafish (Danio rerio)

Abstract: Because of persistent organic pollution in aquatic environments, the widely used organochlorine pesticide endosulfan, which is a potential endocrine disruptor, is expected to pose a significant risk to aquatic organisms. In the present study, we explored the potential endocrine-disrupting risk of β-endosulfan by investigating its effect on the growth, reproduction, plasma vitellogenin, and organ histology of adult zebrafish. We found that, although β-endosulfan did not significantly affect the growth of zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…The results of this study are in concordance with earlier studies that demonstrated a dose-dependent increase in plasma VTG in male zebrafish exposed to -endosulfan (Han et al, 2011). Upregulation of messenger RNA expression of hepatic VTG1 and VTG3 in male zebrafish exposed to tribromophenol and 2,4-dichlorophenol was also noticed earlier Ma et al, 2012).…”
Section: Discussionsupporting
confidence: 95%
“…The results of this study are in concordance with earlier studies that demonstrated a dose-dependent increase in plasma VTG in male zebrafish exposed to -endosulfan (Han et al, 2011). Upregulation of messenger RNA expression of hepatic VTG1 and VTG3 in male zebrafish exposed to tribromophenol and 2,4-dichlorophenol was also noticed earlier Ma et al, 2012).…”
Section: Discussionsupporting
confidence: 95%
“…A study of Hanson et al (2007) showed the adverse effects of lindane, pentachlorophenol and propoxur on the growth of Nile tilapia, African catfish and Bagrid catfish Chrysitchtys nigrodigitatus. On the contrary a concentration of 10 ng/L of b-endosulfan did not affect the growth of zebrafish (Han et al 2011). Several factors can explain the delay observed in growth of fish exposed to the pesticides tested, such as the difference of feed intake (Wang et al 1998;Qian et al 2002;Lal et al 2013) or the difference in the food metabolism (Qian et al 2002).…”
Section: Growth and Feed Efficiencymentioning
confidence: 90%
“…Mlambo et al (2009) reported that DDT exposure caused disorganization of seminiferous lobules in the testes of adult Mozambique tilapia (O. mossambicus). Testes degeneration and sperm necrosis were seen in the testes tissues of fish treated with beta endosulfan (Han et al 2011).…”
Section: Deltamethrintreated Groupmentioning
confidence: 98%
“…Atretic follicles were detected in the ovary of fish treated with beta endosulfan. These atretic follicles exhibited characteristic degenerative changes, including decreased vitellogenesis, oocyte membrane folding, and an increase in the number and size of follicular cells (Han et al 2011).…”
Section: Deltamethrintreated Groupmentioning
confidence: 99%